1997
DOI: 10.1016/s0194-5998(97)70358-9
|View full text |Cite
|
Sign up to set email alerts
|

Meningitis after cochlear implantation in Mondini malformation☆☆☆★

Abstract: Although the potential for CSF leakage and subsequent meningitis after cochlear implantation in the malformed cochlea has been recognized, this complication has not been previously reported. We report a case of CSF otorhinorrhea and meningitis after minor head trauma developing 2 years after cochlear implantation in a child with Mondini malformation. Leakage of CSF was identified from the cochleostomy around the electrode of the implant, and this leak was sealed with a temporalis fascia and muscle plug. Althou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
21
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 4 publications
2
21
0
1
Order By: Relevance
“…This is in keeping with several reports in the literature on the success of cochlear implantation for inner ear malformations (3,12,15,(30)(31)(32)(33).…”
Section: Discussionsupporting
confidence: 91%
“…This is in keeping with several reports in the literature on the success of cochlear implantation for inner ear malformations (3,12,15,(30)(31)(32)(33).…”
Section: Discussionsupporting
confidence: 91%
“…Ito et al [1999] and Molter et al [1993] reported no CSF gushers in any subjects with congenitally malformed cochleae. Effective control of the CSF leak is important due to increased risk of CSF otorhinorrhoea [Hoffman et al, 1997] and/or otogenic meningitis [Page and Eby, 1997;Weber et al, 1998].…”
Section: Introductionmentioning
confidence: 99%
“…Sennaroglu and Saatci [2002] classified 23 radiological cases of congenital malformations in descending order of severity; Michel deformity (cochlear aplasia), common cavity (convergence of the cochlea and vestibule into a common rudimentary cavity, often with abnormal semicircular canals) and incomplete partition, with 2 subdivisions IP-I (cystic cochleovestibular malformation) and IP-II (classical Mondini dysplasia). Carlo Mondini (1971) first described these cochleae with one and a half turns and absent interscalar septum (incomplete partition) [Page and Eby, 1997], thought to be the result of arrested labyrinthine development in the seventh fetal week [Mitchell and Rubin, 1985]. It is one of the most common congenital cochlea abnormalities seen [Cohen and Waltzman, 2000] and can be unilateral or bilateral [Mitchell and Rubin, 1985], with a stable or progressive course of hearing loss.…”
mentioning
confidence: 99%
“…Meningitis following implantation in Mondini dysplasia has been reported (Page and Eby, 1997), with CSF leakage from around the site of the cochleostomy found six months after implantation. Phelps et al (1994) undertook a detailed study of 20 patients with malformed cochleae in an attempt to quantify the risk of meningitis associated with different anomalies.…”
Section: Discussionmentioning
confidence: 99%